1997
DOI: 10.1046/j.1365-2648.1997.1997025412.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the reported early experiences of student nurses with those of a group of people outside the helping professions

Abstract: In order to investigate the psychodynamic concepts of "reparation' and "compulsive caring' as possible motivations for a career in nursing, a questionnaire was given to two groups of respondents, 115 nursing students and 97 people not involved in any of the helping professions. Both groups were asked whether or not they had experienced specific, potentially distressing events and circumstances in their childhood and teenage years. The null hypothesis was that there would be no statistically significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Motivation to nurse has been discussed as a predictive variable and selection criterion but Land (1993) found a qualitative difference between those who ‘always wanted to nurse’, which could be constructed as a ‘need to be needed’, and those who had a genuinely realistic view of nursing. The ‘need to be needed’ argument was reported in a study by Phillips (1997), whose research suggested that nursing students had a greater number of recollected adverse life experiences compared with a comparable group of students outside the helping professions. These early experiences could influence decisions to seek a career within a perceived therapeutic community, but were likely to be a predictive factor in occupational stress.…”
Section: Introductionmentioning
confidence: 99%
“…Motivation to nurse has been discussed as a predictive variable and selection criterion but Land (1993) found a qualitative difference between those who ‘always wanted to nurse’, which could be constructed as a ‘need to be needed’, and those who had a genuinely realistic view of nursing. The ‘need to be needed’ argument was reported in a study by Phillips (1997), whose research suggested that nursing students had a greater number of recollected adverse life experiences compared with a comparable group of students outside the helping professions. These early experiences could influence decisions to seek a career within a perceived therapeutic community, but were likely to be a predictive factor in occupational stress.…”
Section: Introductionmentioning
confidence: 99%
“…(1998) explored the prevalence of unwanted sexual experiences reported by student nurses and found that of a cohort of 109 second year nursing students nearly 1 in 2 (47.6%) reported some form of unwanted sexual experience, with 1 in 8 women and 1 in 10 men reporting someone having sexual intercourse with them against their will. Rew & Christian (1993) when surveying 87 nursing students found 47% of women and 38% of men had experienced one or more unwanted sexual experience in childhood, whilst in a comparative study undertaken by Phillips (1997), between a group of student nurses ( n = 115) and people outside the helping profession ( n = 97), 10 of the nurses as opposed to 2 of the control group recalled experiences of sexual abuse. Interestingly a study carried out in the US (Elliot & Guy 1993) investigated the extent of childhood trauma among female mental health professionals working as therapists compared with women working in other professions and concluded that mental health professionals were no more likely to correctly identify themselves as sexually abused than non‐mental health professionals.…”
Section: Through the Looking Glass?mentioning
confidence: 99%
“…The crux of psychodynamic theory is that the development of a sense of self is mediated by our early childhood experiences (Phillips 1997), and as a minimum Gallop & O’Brien (2003) believe that mental health nurses need to understand how we become who we are and how our own history and that of the clients are re‐enacted and modified within therapeutic interactions. It is the practitioner's responsibility to acknowledge the complexity of the human experience, and to navigate the therapeutic relationship.…”
Section: Through the Looking Glass?mentioning
confidence: 99%
See 2 more Smart Citations